Low phosphorus tolerance mechanisms: Phosphorus recycling and photosynthate partitioning in the tropical forage grass, Brachiaria hybrid cultivar mulato compared with rice - Nanamori, M; Shinano, Takuro; Wasaki, J; Yamamura, T; Rao, Idupulapati M.; Osaki, M (Oxford University Press, 2004)
The Brachiaria hybrid cv. Mulato is well adapted to low-fertility acid soils deficient in phosphorus (P). To study the grassy forage’s mechanisms for tolerating low P supply, we compared it with rice (Oryza sativa L. cv. Kitaake). We tested by using nutrient solution cultures, and quantified the effects of P deficiency on the enzymatic activities of phosphohydrolases and on carbon metabolism in P-deficient leaves. While P deficiency markedly induced activity of phosphohydrolases in both crops, the ratio of inorganic phosphorus to total P in leaves was greater in Brachiaria hybrid. Phosphorus deficiency in leaves also markedly influenced the partitioning of carbon in both crops. In the Brachiaria hybrid, compared with rice, the smaller proportion of 14C partitioned into sugars and the larger proportion into amino acids and organic acids in leaves coincided with decreased levels of sucrose and starch. Hence, in P-deficient leaves of the Brachiaria hybrid, triose-P was metabolized into amino acids or organic acids. Results thus indicate that the Brachiaria hybrid, compared with rice, tolerates low P supply to leaves by enhancing sugar catabolism and by inducing the activity of several phosphohydrolases. This apparently causes rapid P turnover and enables the Brachiaria hybrid to use P more efficiently.